Maximization of Economic Cooperation among Moslem Countries and the Urgency of “Islamic Common Market” - Mohammad B.Hendrie Anto (Jurnal Iqtisad, 2003)
“O humankind! We have created you from male and female, and made you into nations and tribes that you may know one another. Verily, the most honorable of you with Allah is that (believer) who has at-taqwa” (al-Hu¬jurat: 13)